SPECIFICS OF THE EDUCATIONAL PROCESS AND ITS IMPACT ON THE FORMATION OF THE PERSONALITY OF YOUNG CHILDREN SCHOOL AGE IN CONDITIONS OF DEPRIVATION (Pedagogy of Higher and Secondary Education, 2003)
No abstract.